TRI HITA KARANA MENINGKATKAN KUALITAS MODAL MANUSIA DARI PERSFEKTIF KESEHATAN - Artana, I Wayan (PIRAMIDA; Vol 10 No 2 (2014): Jurnal PIRAMIDA, 2014)
Human capital contains the values found in the human beings themselves. Human capital has a value that can be used to live their life to become more comfortable. The level of health is a very important human capital as a fundamental support to be able to reflect other values in order to achieve successful society and individuals. Health as defined by the World Health Organization (WHO) which initially defined that healthy means to be physically, psychologically, socially healthy, and free of defects. However, It has been now added with spiritually healthy. The health of human capital is not only affected by genetics, health care facilities and infrastructure, as well as the environment, but also strongly influenced by the behavior or culture of human capital themselves, as well as the culture of the group in which human capital is located. Culture of Tri Hita Karana (THK) can improve the character of human capital by means of improving their health values.
Keywords: human capital, Tri Hita Karana, health